Thermodynamics of the Second Ionization of Piperazine- N,N´ -Bis(2-Ethanesulfonic Acid) in Water and in Aqueous Methanol - Jumean, F.H. (Asian Journal of Chemistry, 2010)
Apparent values for the free energy, enthalpy, entropy, and heat capacity for the second ionisation of the biological buffer piperazine-N,N´-bis(2-ethanesulfonic acid) (pipes) were obtained in water and in solutions containing 10, 20 and 30% (w/w) methanol. The free energy values were obtained from potentiometric measurements. The other thermodynamic parameters were obtained spectrophotometrically, making use of the pronounced thermochromacy of the system neutral red-pipes. Thermodynamic values for the transfer of pipes from water to the methanolic solvents were calculated. The medium effect term, log (mγA-/mγHA-), was estimated as a function of the acid and base forms of the pipes species, for each solvent medium. Conclusions were drawn regarding the charge disposition on the acid and base forms in pipes as well as the nature of interactions between the two pipes species and the solvent.